Puppet Horn Craft in Pucang Village Magelang Regency: Aesthetic and Production Process Study - Sanjani, Muhamad Ludfi (Universitas Negeri Semarang, 2017)
Nowdays puppet is developing and produce new form as handicraft such as a decoration/souvenir which produced by craftsman of puppet craft horn at Pucang Village, Magelang Regency. The objective of the research is to describe an aesthetics form and process production of puppet craft horn at Pucang Village, Magelang regency. The methodology used in this research was interactive analysis. The result of the research showed there are some aspects in the aesthetic form of puppet craft horn at Pucang village, they are: design/gagrag, structures/parts of puppet, arrangement and the colour was simpler than wayang which used for its reference, but every character could be known. The process production still use conventional technique relies on craftsmen skill. Process production of puppet craft horn dived into three major points: 1) early stage 2) formation the characters of puppet 3) finishing. The suggeation proposes by researcher are: 1) for the craftsmen at pucang village should be defining and developing their creation of puppe whether it's form or the materials, 2) for the Department of Tourism and Culture, should be used it for exclusive handicraft or souvenir from Magelang.